5(x-1)=3(x+9)

Simple and best practice solution for 5(x-1)=3(x+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-1)=3(x+9) equation:


Simplifying
5(x + -1) = 3(x + 9)

Reorder the terms:
5(-1 + x) = 3(x + 9)
(-1 * 5 + x * 5) = 3(x + 9)
(-5 + 5x) = 3(x + 9)

Reorder the terms:
-5 + 5x = 3(9 + x)
-5 + 5x = (9 * 3 + x * 3)
-5 + 5x = (27 + 3x)

Solving
-5 + 5x = 27 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-5 + 5x + -3x = 27 + 3x + -3x

Combine like terms: 5x + -3x = 2x
-5 + 2x = 27 + 3x + -3x

Combine like terms: 3x + -3x = 0
-5 + 2x = 27 + 0
-5 + 2x = 27

Add '5' to each side of the equation.
-5 + 5 + 2x = 27 + 5

Combine like terms: -5 + 5 = 0
0 + 2x = 27 + 5
2x = 27 + 5

Combine like terms: 27 + 5 = 32
2x = 32

Divide each side by '2'.
x = 16

Simplifying
x = 16

See similar equations:

| 32r-80z= | | 30m-120= | | s-15=-33 | | 24v+32w= | | 9p+21= | | 3x+2+5x-5=25 | | 6x+2y+6=0 | | 12x+8=10x+40 | | 10x^3+8x^2+2x=0 | | 9x+6-10x-25=30 | | 12n+2=4n+3 | | -3x+4=(-2)x+(-19) | | 4f-24g= | | 4+12/x=7 | | 12n+5=4n+6 | | -27-3x=6x+24 | | -81-9x=21+8x | | 10r-15s= | | 12n+3=4n-6 | | 9x^2-79x-130=0 | | 14c+28d= | | 7y+6x-3=3y-3x+2 | | n+(-20)=7-n | | 84-3x=3x+24 | | 4y+6z= | | 35-3x=2x | | 61-3x=61-3x | | 8n+24= | | 5e-5f= | | 3a-3b= | | 79-3x=2x-9 | | 12x-2=7x |

Equations solver categories